Impact of Sharia and Emotional Marketing to Customers Decision of Islamic Banking Products - M Disastra, Ganjar; Juni Priansa, Donni (International Journal of Engineering and Technology, 2019)
The development of Islamic banking industry in Indonesia continued to show a positive trend in line with the development of the Islamic banking system in accordance with the Indonesian market. Islamic banking could encourage the growth of the regional economy in order to achieve balanced economic structure. However, the performance of the Islamic banking industry is still far below the conventional banking industry performance. This study aimed to analyze the sharia marketing, emotional marketing, and customers decision of Islamic banking products and to analyze the influence of sharia marketing and emotional marketing to customers decision of Islamic banking products. This study is a descriptive-verification with design research is causality. Unit analysis of this study are customers of Islamic banks that spread at Bank Muamalat Indonesia; Bank Syariah Mandiri; Bank CIMB Niaga Syariah; BCA Syariah; and Bank Mega Syariah. Data analysis techniques used in this research is path analysis. Results of this study showed that sharia marketing and emotional marketing has positive and significant impact to customers decision of Islamic banking products, either partially or simultaneously. These findings illustrate that the Islamic banking industry needs to be improve its performance through improved customers decision of Islamic banking products, which the supported by the strengthening aspects of sharia and emotional marketing.Â